Refractive index of graphene AA and AB stacked bilayers under the influence of relative planar twisting. (26th October 2021) - Kumar, Amrit; Manjuladevi, V; Gupta, R K
Abstract: The optical properties of graphene in monolayer and bilayer structure is essential for the development of optical devices viz surface plasmon resonance (SPR) based bio-sensors. The band structure of the twisted bilayer graphene (BLG) is remarkably different than the normal AA or AB stacking. This provides an opportunity to control the optical and electrical properties of BLG by applying an in-plane twist to one of the layer relative to other in a BLG system. Here, we calculated the refractive index (RI) of AA and AB stacking of BLG system using density functional theory. Though the spectrum for AA stacking shows some similarity with that of monolayer graphene, the spectrum for AB stacking was found to be remarkably different. The spectrum of AB stacked layer is red-shifted and the absorption peaks in low energy regime increases nearly by three-folds. A large dependency of the twist angle on RI of twisted BLG were found. Based on the calculation, a schematic of phase diagram showing material behavior of such twisted BLG systems as a function of twist angle and photon energy was constructed. The twisted AA stacked BLG shows largely dielectric behavior whereas the twisted AB stacked BLG shows predominately semimetallic and semiconducting behavior. This study presents a RI landscape of twisted BLG dependent on important parameters viz photon energy and inplane relative twist angle. Our studies will be very useful for the design and development of optical devices employing BLG systems particularly SPR based bio-sensors which essentially measures change in RI due to adsorption of analytes.